An assessment tool for effective learning of Colegio de la Purisima Concepcion high school students - Baes, Glenn Bermejo (Iloilo City University of the Philippines in the Visayas, 2005)
The main purpose of the study was to design an assessment tool for the affective of Colegio de la Purisima Concepcion High School students. The first part of the study established the back-ground and context of the research including its significance. It included the presentation of foreign and local models of assessment. The researcher learned relevant insights and lessons from these models, which were helpful in developing the tool. Forty Seven (47) teacher respondents from Colegio de la Purisima Concepcion participated in the study. Thirty (30) college students were dry run of the tool and one hundred sixty six (166) CPC High School students were rated in the actual rating activity of the assessment tool. The design of the tool went through several processes. The first process was the definition of the constructs, which in this study, are given. They were taken from the CPC High School core values as expressed in the mission, vision and ideal CPC High School graduate. The second process is the formulation of the indicators of the construct. These constructs provided concrete behavioral manifestations for rating. In the instrumentation process, the formulation of standards, rating scale, values and equivalents was made. Tool validity, reliability and viability directed the last phase of the design. A panel of experts and a Graduate School subject teacher of the researcher in Psychological Testing validated the content of the tool. To ascertain the reliability of the tool, it was subjected to a dry run to thirty (30) college teachers from Colegio de la Purisima Concepcion. These thirty (30 respondents did not participate in the final study. The result of the dry run was processed and encoded by the Cronbach Alpha Statistics. An actual rating activity established the viability of the assessment tool. Feedbacks from teacher and class adviser respondents and other factors prompted refienment and revisions to the said tool for its effective use. The out-put of this research is a Rater's Guide of the Assessment Tool where details of procedures for implementation and interpretation are stated. Indeed, the research work proved that affective learning of CPC High School students could be assessed through a valid, reliable, and viable assessment tool. This study can be useful to the Guidance Service of the School in terms of creating developmental or interventon programs based on the results the assessment tool can provide. The assessment tool fr affective learning of CPC High School students showed how they may be served effectively through CPC High School holistic educational thrust that develops not only their intellect but also their affective faculty.
Special Problem--(M.Ed.- Guidance)--College of Arts and Sciences, University of the Philippines in the Visayas, April 2005.2005.
Keywords: Learning